Cell Stress Profile During Metabolite Production by Saccharomyces cerevisiae Catanduva-1 in Sugarcane Wort - dos Santos, Nislene Pires; da Silva, Geisa Alves; Cardoso, Claudia Andrea Lima; Batistote, Margareth (Orbital: The Electronic Journal of Chemistry, 2018)
During ethanol production, yeasts are subjected to a number of stress factors - among them high substrate concentrations and high temperatures - while displaying an ability to adapt to the adverse conditions found during fermentation. This study evaluated the metabolic profile exhibited by Saccharomyces cerevisiae Catanduva-1 during fermentation. Yeast cells were cultured in 2% YPD medium, incubated in a shaker at 30 °C and 250 rpm for 10 h, and subsequently centrifuged and washed in saline solution for biomass harvesting. Fermentation experiments were performed at 18, 22, and 25°Bx sterilized at 120 °C for 20 min. Biomass was reinoculated into wort and incubated in a shaker at 30 °C and 40 °C at 250 rpm. Evaluation of fermentation parameters revealed better fermentative performance at 30 °C for all substrate concentrations investigated. Under the test conditions, cellular stress was observed at 40 °C. A superior ethanol production profile was obtained at 22°Bx and 30 °C. Glycerol accumulation was highest at 25°Bx and 40 °C. DOI: http://dx.doi.org/10.17807/orbital.v10i1.1029